Nie.Przedstawialne. Uwagi o ciałach boskim, zwierzęcym i ludzkim w komiksie Roberta Crumba Księga Genesis - Kaźmierczak, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The paper refers to the comics entitled The Book of Genesis illustrated by Robert Crumb. The main hypothesis relates to the following statement: Robert Crumb’s visual interpretation of The Book of Genesis is dominated by an anthropocentric perspective. The article consists of three main parts: remarks about the body of God, about the body of animals and about the body of humans. The representations of the body show how the process of desacralization of The Book of Genesis becomes real. Crumb’s style seems to put the dominant religious interpretation of the Book into brackets.